2003
DOI: 10.1038/sj.npp.1300354
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Attenuates the Antidepressant-Like Effect Mediated by the Activation of 5-HT1A Receptor in the Mouse Tail Suspension Test

Abstract: Several lines of evidence have indicated that the prevalence of depression in diabetic subjects is higher than that in the general population, however, little information is available on the effects of antidepressants in diabetes. In the present study, the antidepressantlike effect mediated by the activation of 5-HT 1A receptors was examined using the tail suspension test in streptozotocin-induced diabetic mice. Long-lasting increases in 5-HT turnover rates were observed in the diabetic mouse midbrain and fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
33
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 44 publications
5
33
1
1
Order By: Relevance
“…had no significant effect on the duration of immobility in the tail suspension test in mice, which is consistent with our previous reports (8,9). Aripiprazole (0.3 mg / kg, i.p.)…”
supporting
confidence: 82%
See 2 more Smart Citations
“…had no significant effect on the duration of immobility in the tail suspension test in mice, which is consistent with our previous reports (8,9). Aripiprazole (0.3 mg / kg, i.p.)…”
supporting
confidence: 82%
“…These metabolic changes strongly limit the use of these class of atypical antipsychotic drugs. Since aripiprazole might be an important therapeutic option for treatment-resistant depressive disorders due to its favorable side-effect profile, we investigated the effect of aripiprazole alone or in combination with the sub-effective dose of fluoxetine (8,9) on the duration of immobility in the mouse tail suspension test. Moreover, we also examined the influence of aripiprazole on glucose metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT1A and 5-HT2A receptors have been shown to play a crucial role in the regulation of serotonergic neurotransmission and the mechanism of action of several ADs, including SSRIs, monoamine oxidase inhibitors, and tricyclics (Middlemiss et al, 2002;Hensler, 2006). Furthermore, pretreatment with antagonists of 5-HT1A and 5-HT2A receptors has been shown to antagonize the action of the SSRIs in the TST in mice (Miyata et al, 2004). Thus, we examined the influence of the pretreatment of mice with the 5-HT1A receptor antagonist WAY100635 (Forster et al, 1995) and the 5-HT2A/2C receptor antagonist ritanserin (Hoyer et al, 1994) by using TST.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Animal models of type 2 diabetes associated depression also shows similar characteristics. 48 The effect of NE on diabetes associated depression is far from being clear. Some studies, have reported a change in NE concentration in both depressed and diabetic animals.…”
Section: Discussionmentioning
confidence: 99%